Elastomer, insole and preparation method thereof
By using high-temperature nucleating agents and processing aids in the preparation of the midsole, the problem of low midsole preparation efficiency is solved, and the rapid shaping and performance improvement of the midsole is achieved.
Patent Information
- Application Number
- CN202411566724.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2024-12-27
AI Technical Summary
In the existing midsole preparation method, the secondary molding setting time is long, which affects the preparation efficiency.
The use of high-temperature nucleating agents and processing aids to promote the rapid crystallization of EVA and POE materials, shorten the cold pressing and shaping time, and improve the fluidity and viscosity of the midsole through specific components and process flow, and improve the hot pressing and cold pressing processes. efficiency.
It significantly shortens the cold pressing and setting time of the midsole, improves the preparation efficiency, and improves the performance of the midsole, including higher fluidity and viscosity, ensuring that the material is foamed and cured within the specified time.
Smart Images

Figure BDA0005119442400000021 
Figure BDA0005119442400000071 
Figure BDA0005119442400000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of shoe materials, and in particular to an elastomer, a midsole and a preparation method thereof. Background Art
[0002] The midsole refers to a part made by the "small foam secondary molded midsole" CMP technology. This midsole is mostly made of EVA ethylene-vinyl acetate copolymer material mixed with additives, made into granules by a granulator, and then molded. The midsole is widely used in sports goods and casual shoes due to its good stability and comfort.
[0003] Chinese patent application 202010875118.4 discloses a method for preparing a secondary compression-molded foamed sole, which comprises preparing EVA rice for primary compression-molding foaming to obtain a foamed embryo with a surface temperature of not less than 130°C; placing the foamed embryo into a hydraulic mold, closing the mold, pushing it into the heating station of a secondary foaming molding machine, pressurizing, heating, and then transferring the hydraulic mold to a cooling station, pressurizing, and cooling the mold with water, with a molding time of 150 seconds to 400 seconds, pulling out the mold, taking out the finished product, and obtaining a foamed sole.
[0004] In this case, the foaming ratio of the first molding is greater than that of the hydraulic mold, so that the size of the foamed embryo is consistent with the size of the hydraulic mold, so that the foamed embryo just taken out of the mold is matched with the hydraulic mold of the same code segment, and by immediately transferring to the hydraulic mold process step, the oil pressure heating time is greatly shortened, reducing energy consumption, and the surface is not crystallized, so it is easier to emboss the pattern and the production time is short.
[0005] Chinese patent application 202210568715.1 discloses a wear-resistant, lightweight, anti-slip, highly soft and elastic shock-absorbing EVA foam sole material, and its preparation method and application, wherein the sole material includes 40 to 60 parts of ethylene-vinyl acetate copolymer; 10 to 20 parts of polyolefin elastomer; 5 to 10 parts of ethylene-acrylate rubber; 20 to 30 parts of modified thermoplastic elastomer; 5 to 10 parts of wear-resistant agent; 1 to 2.5 parts of zinc oxide whisker.
[0006] The EVA foam sole material of this solution has good wear resistance and anti-slip properties, and can directly touch the ground without the need to combine with rubber. At the same time, it has low hardness, low specific gravity, and good rebound and shock absorption properties, meeting the soft and light comfort requirements.
[0007] The problem that this solution needs to solve: How to improve the preparation efficiency of the midsole. Summary of the invention
[0008] The purpose of the present invention is to provide an elastomer, a midsole and a preparation method thereof, which promotes crystallization by physical means, so that the high-temperature crystallized components in the components produce crystal nuclei in the early stage of the cold pressing stage, provide molding crystal nuclei for low-temperature crystallized materials such as EVA and POE, promote their rapid crystallization, and thus shorten the time for secondary shaping.
[0009] To achieve the above object, the present application discloses an elastomer, which comprises 40 to 50 parts by weight of a high-temperature nucleating agent, 5 to 10 parts by weight of a processing aid, and 40 to 50 parts by weight of an EVA carrier;
[0010] The high temperature nucleating agent is selected from at least one of polyethylene, talc and silicon dioxide;
[0011] The processing aid is selected from at least one of microcrystalline wax and stearic acid;
[0012] The EVA is selected from at least one of EVA7470M, EVA360, and EVA7350.
[0013] The high-temperature nucleating agent is made into an elastomer, and a high-crystallinity component is formed within the elastomer, which will solidify rapidly during cold pressing, shortening the cold pressing and shaping time of the midsole; combined with processing aids, it can help the flow of high-crystallinity components and reduce performance problems caused by uneven distribution; using EVA as a carrier, when the same as the EVA model of the midsole, can help the fusion and flow of the elastomer component; when the EVA model of the midsole is different, the two types of EVA can complement each other and further improve the performance of the midsole.
[0014] Preferably, the preparation method of the elastomer is: mixing a high temperature nucleating agent with EVA, heating, stirring and dissolving, adding a processing aid, continuing stirring, cooling, and granulating to obtain the elastomer.
[0015] In addition, a midsole is also disclosed, which comprises the following components by weight:
[0016]
[0017] The EVA is selected from at least one of EVA7470M, EVA360, and EVA7350;
[0018] The POE is selected from at least one of ENGAGE8003, ENGAGE8440, and ENGAGE8200.
[0019] Preferably, the calcium carbonate composition is prepared by mixing calcium carbonate and EVA7470M in a mass ratio of 1:1, kneading at 90±10° C. for 0.4 h, and granulating to obtain the calcium carbonate composition;
[0020] The titanium dioxide composition is prepared by mixing titanium dioxide and EVA7470M in a mass ratio of 3:2, kneading the mixture at 90±10° C. for 0.4 h, and granulating the mixture to obtain the titanium dioxide composition.
[0021] Preferably, the preparation method of LH-DH9-CMP is: mixing azodicarbonamide, zinc stearate, chlorosulfonated polyethylene, petroleum resin, and ethylene-vinyl acetate copolymer in a mass ratio of 50:15:5:5:25 at 100±10°C for 0.4h, mixing, and granulating to obtain LH-DH9-CMP;
[0022] The preparation method of LH-CAT is as follows: zinc oxide, urea ester, calcium carbonate, and ethylene-vinyl acetate copolymer are mixed and kneaded at a mass ratio of 30:5:10:55 at 100±10° C. for 0.4 h, mixed, and granulated to obtain LH-CAT.
[0023] In addition, a method for preparing a midsole is also disclosed, comprising the following steps:
[0024] Step 1: EVA, POE, elastomer, calcium carbonate composition, titanium dioxide composition, di-tert-butyl peroxide diisopropylbenzene, stearic acid, LH-DH9-CMP, and LH-CAT are mixed and kneaded to obtain a rubber compound;
[0025] Step 2: Add the mixed rubber into a foaming mold, vulcanize, cool and shape, and obtain a foamed product;
[0026] Step 3: Add the foamed product into a mold, perform hot pressing and cold pressing, and obtain a midsole;
[0027] Wherein, the hot pressing time is 480s, and the cold pressing time is 400s.
[0028] Preferably, the mixing temperature in step 1 is 115-120° C. and the mixing time is 10-15 min.
[0029] Preferably, the vulcanization temperature in step 2 is 165-170° C., and the vulcanization time is 10-12.5 min.
[0030] Preferably, in step 3, the hot pressing temperature is 165-170°C, and the cold pressing temperature is 15-20°C.
[0031] The beneficial effects of the present invention are:
[0032] The present invention provides an elastomer, a midsole and a preparation method thereof. A high-fluidity polymer resin is used to match a primary foaming embryo of the elastomer to have higher fluidity and viscosity; during hot pressing, the mold filling speed of the foaming embryo can be greatly improved and the heating time can be shortened; and during cold pressing, components with high crystallinity in the elastomer will rapidly solidify as the temperature rapidly drops, thereby driving the product to be quickly shaped, and effectively shortening the cold pressing shaping time. DETAILED DESCRIPTION
[0033] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0034] Product information:
[0035] EVA7470M, EVA360, EVA4325: provided by Taiwan Plastics Corporation;
[0036] ENGAGE8003, ENGAGE8440, ENGAGE8450: provided by Jihong International Co., Ltd.
[0037] Diisopropyl ditert-butyl peroxide: provided by Hunan Fangruida Technology Co., Ltd.
[0038] Unless otherwise specified, the preparation methods of LH-DH9-CMP, LH-CAT, calcium carbonate composition, and titanium dioxide composition in the examples and comparative examples are as follows:
[0039] LH-DH9-CMP: azodicarbonamide, zinc stearate, chlorosulfonated polyethylene, petroleum resin, and ethylene-vinyl acetate copolymer were mixed in a mass ratio of 50:15:5:5:25, mixed and kneaded at 100°C for 0.4h, mixed, and granulated to obtain LH-DH9-CMP;
[0040] LH-CAT: zinc oxide, urea ester, calcium carbonate, and ethylene-vinyl acetate copolymer were mixed in a mass ratio of 30:5:10:55, mixed and kneaded at 100°C for 0.4h, mixed, and granulated to obtain LH-CAT;
[0041] Calcium carbonate composition: Calcium carbonate and EVA7470M are mixed in a mass ratio of 1:1, mixed and kneaded at 90° C. for 0.4 h, and granulated to obtain a calcium carbonate composition;
[0042] Titanium dioxide composition: Titanium dioxide and EVA7470M were mixed in a mass ratio of 3:2, mixed and kneaded at 90±10° C. for 0.4 h, and granulated to obtain a titanium dioxide composition.
[0043] Example 1
[0044] 45 parts of polyethylene and 45 parts of EVA7470M were mixed, heated to 110°C, stirred and turned over 3 times, 7 parts of microcrystalline wax were added, the mixture was stirred and turned over 3 times, the temperature was lowered to 30°C, and granulated to obtain an elastomer.
[0045] Example 2
[0046] Mix 40 parts of polyethylene and 40 parts of EVA7470M, heat to 110°C, stir and turn the material 3 times, add 10 parts of microcrystalline wax, continue to stir and turn the material 3 times, cool to 30°C, and granulate to obtain an elastomer.
[0047] Example 3
[0048] Mix 50 parts of polyethylene and 50 parts of EVA7470M, heat to 110°C, stir and turn the material 3 times, add 3 parts of microcrystalline wax, continue to stir and turn the material 3 times, cool to 30°C, and granulate to obtain an elastomer.
[0049] Example 4
[0050] It is basically the same as Example 1, except that the high temperature nucleating agent in the elastomer is talcum powder.
[0051] Example 5
[0052] It is basically the same as Example 1, except that the high temperature nucleating agent in the elastomer is silicon dioxide.
[0053] Example 6
[0054] It is basically the same as Example 1, except that the high temperature nucleating agent in the elastomer is prepared by mixing polyethylene and talc in a mass ratio of 1:1.
[0055] Comparative Example 1
[0056] 45 parts of polyethylene were heated to 110°C, stirred and turned over 3 times, 7 parts of microcrystalline wax were added, the mixture was stirred and turned over 3 times, the temperature was lowered to 30°C, and granulated to obtain an elastomer.
[0057] Comparative Example 2
[0058] 45 parts of EVA7470M were heated to 110°C, stirred and turned over 3 times, 7 parts of microcrystalline wax were added, the mixture was stirred and turned over 3 times, the temperature was lowered to 30°C, and granulated to obtain an elastomer.
[0059] Comparative Example 3
[0060] 45 parts of polyethylene and 45 parts of EVA7470M were mixed, heated to 110°C, stirred and turned over 6 times, cooled to 30°C, and granulated to obtain an elastomer.
[0061] Comparative Example 4
[0062] 55 parts of polyethylene and 35 parts of EVA7470M were mixed, heated to 110°C, stirred and turned over 3 times, 12 parts of microcrystalline wax were added, the mixture was stirred and turned over 3 times, the temperature was lowered to 30°C, and granulated to obtain an elastomer.
[0063] Comparative Example 5
[0064] 35 parts of polyethylene and 55 parts of EVA7470M were mixed, heated to 110°C, stirred and turned over 3 times, 3 parts of microcrystalline wax were added, the mixture was stirred and turned over 3 times, the temperature was lowered to 30°C, and granulated to obtain an elastomer.
[0065] Application Example 1-13
[0066] The preparation method of the midsole is:
[0067] Step 1: EVA, POE, elastomer, calcium carbonate composition, titanium dioxide composition, di-tert-butyl peroxide diisopropylbenzene, stearic acid, LH-DH9-CMP, and LH-CAT are mixed and kneaded at a temperature of 120° C. for 13 minutes to obtain a rubber compound; and it should be noted that the elastomers used in Application Examples 1-9 correspond to the elastomers obtained in Examples 1-6 and Comparative Examples 1-3, respectively;
[0068] Step 2: Add the mixed rubber into a foaming mold, vulcanize at 168°C for 10 minutes, cool to 30°C for shaping, and obtain a foamed product;
[0069] Step 3: Add the foamed product into the mold, perform hot pressing at 165° C. for 480 seconds, and then perform cold pressing at 20° C. for 400 seconds to obtain the midsole;
[0070] The composition of the bottom in Application Example 1-13 is shown in Table 1:
[0071] Table 1
[0072]
[0073] It is noted again that the elastomers used in Application Examples 1-11 correspond to the elastomers prepared in Examples 1-6 and Comparative Examples 1-5, respectively. The difference between Application Examples 1-11 is only the composition of the elastomers, and the remaining midsole components and the amount of each component added are the same.
[0074] Application Example 14
[0075] It is basically the same as Application Example 1, except that the added amount of the elastomer is 5 parts.
[0076] Application Example 15
[0077] It is basically the same as Application Example 1, except that the added amount of the elastomer is 3 parts.
[0078] Application Example 16
[0079] It is basically the same as Application Example 1, except that the added amount of the elastomer is 7 parts.
[0080] Application Example 17
[0081] It is basically the same as Application Example 1, except that the added amount of the elastomer is 1 part.
[0082] Application Example 18
[0083] It is basically the same as Application Example 1, except that no elastomer is added to the midsole.
[0084] Application Example 19
[0085] The method is basically the same as Application Example 1, except that the polyethylene, microcrystalline wax and EVA7470M are not made into elastomers in advance, but are directly added to CMP without changing their quality.
[0086] Application Example 20
[0087] It is basically the same as Application Example 1, except that the EVA in the midsole is EVA360.
[0088] Application Example 21
[0089] It is basically the same as Application Example 1, except that the POE in the midsole is ENGAGE8440.
[0090] Application Example 22
[0091] It is basically the same as Application Example 1, except that the EVA in the midsole is EVA4325.
[0092] Application Example 23
[0093] It is basically the same as Application Example 1, except that the POE in the midsole is ENGAGE8450.
[0094] Performance Test:
[0095] Hardness: Use a C-type hardness tester with a 1kg weight to test, evenly select 5 test points, and take the middle value. The standard physical property is 38-42Shore.C;
[0096] Tensile strength: Cut out a 3-4mm thick test piece, cut it into a dumbbell shape, clamp the head and tail with a tensile testing machine, input the test thickness and width of the material, stretch it at a speed of 500mm / min until it breaks, and get the tensile strength of the material. The standard physical property is greater than or equal to 20kg / cm2 ;
[0097] Peel strength: Cut the test piece in the middle, clamp the two sides of the section with a tensile machine, input the thickness and width of the material, stretch it at a speed of 50mm / min until it breaks, and obtain the peel strength of the material. The standard physical property is greater than or equal to 1.7kg / cm;
[0098] Compression distortion: Punch the sample into a cylindrical shape, record the thickness before the test, clamp it in a fixture with a thickness of 50% of the material thickness (the thickness is controlled by a metal gasket), tighten the fixture, put it in a 50°C oven, heat it for 6 hours, take it out of the oven, take the sample out of the fixture, cool and relax it for 30 minutes, then record the test thickness, calculate the compression distortion of the sample using a compression distortion calculation company, and the standard physical property is less than or equal to 80%;
[0099] Thermal shrinkage rate: Take a sample and mark a length scale, put it into a 70℃ oven for 1 hour, take it out and cool it for 30 minutes, then test the marked scale size and calculate the thermal shrinkage rate of the material. The standard physical property is less than or equal to 2%;
[0100] The test results of each embodiment and comparative example are shown in Table 2:
[0101] Table 2
[0102]
[0103]
[0104] Conclusion analysis:
[0105] 1. It can be seen from Application Examples 1-3 and Application Examples 10-11 that in the elastomer, as the addition amount of high-temperature nucleating agent, processing aid and EVA changes, their influence on the performance of the midsole is also constantly changing within the physical property standards; however, it can be seen from Application Examples 10-11 that as the content of high-temperature nucleating agent and processing aid continues to increase, after reaching a certain amount, the improvement of the physical properties of the midsole tends to be stable; and as the content of high-temperature nucleating agent and processing aid decreases, it is impossible to complete the foaming and curing process within a limited time, thereby affecting the physical properties of the midsole.
[0106] 2. It can be seen from Application Examples 1 and 4-6 that the selection of high-temperature nucleating agent in elastomer will not have much effect on the physical properties of the mid-substrate in terms of a single component. However, it can be seen from Application Example 10 that when the high-temperature nucleating agent is a mixture of polyethylene and talcum powder in a mass ratio of 1:1, the improvement in the physical properties of the obtained elastomer is far greater than the simple addition of the improvements brought by a single component. This shows that there is a synergistic relationship between polyethylene and talcum powder in the high-temperature nucleating agent.
[0107] Further observation of Application Examples 18-19 shows that when no elastomer is added or the high-temperature nucleating agent, processing aid and EVA in the elastomer are directly added to the midsole, due to the lack of high crystallinity components, the foaming and curing processes of the midsole blank cannot be completed normally, thereby affecting the physical properties of the midsole.
[0108] 3. It can be seen from Application Examples 1 and 7-9 that when the three components of the high-temperature nucleating agent, the processing aid and EVA in the elastomer are used in pairs, the physical properties of the obtained midsole are all lower than the physical property standards and cannot be used. This is because when EVA is missing, the elastomer cannot be granulated; when the high-temperature nucleating agent is missing, the elastomer cannot make the midsole complete foaming and curing within the specified time, thereby affecting the physical properties of the midsole; when the processing aid is missing, the fluidity of the elastomer in the material will be reduced, the processing efficiency will be reduced, and the physical properties of the midsole will be affected.
[0109] 4. It can be seen from Application Examples 1 and 12-13 that in the composition of the midsole components, the change in the content of each component will also affect the physical properties of the CMP;
[0110] Further observation of Application Example 1 and Application Examples 14-17 shows that as the amount of elastomer added increases, the physical properties of the midsole will gradually increase, but after reaching a certain amount, the increase in elastomer has little effect on the increase in physical properties; at the same time, when the amount of elastomer is insufficient, the midsole cannot be improved within the specified time during the hot pressing and cold pressing processes, and thus the physical properties cannot meet the midsole physical property standards.
[0111] 5. It can be seen from Application Examples 1 and 20-23 that the selection of EVA and POE is also an important choice in the composition of the midsole. It can be seen from Application Examples 1 and 20-21 that when EVA is EVA7470M, EVA360 or POE is ENGAGE8003, ENGAGE8440, the physical properties of the prepared midsole are relatively close. However, when observing Application Examples 22-23, when EVA4325 or ENGAGE8450 is selected, the performance of the midsole will be reduced, but the performance can also meet the midsole physical property standards. It is speculated that this may be due to the structural differences between EVA models or other reasons.
[0112] At the same time, by observing Application Example 1 and Application Example 20, it can be seen that when the elastomer and the EVA type of the midsole are different, the compatibility of the components can be improved between the two types of EVA, thereby further improving the performance of the midsole.
[0113] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. An elastomer, characterized in that: The invention is prepared from 40 to 50 parts of a high temperature nucleating agent, 5 to 10 parts of a processing aid, and 40 to 50 parts of EVA by weight. The high temperature nucleating agent is selected from at least one of polyethylene, talc and silicon dioxide; The processing aid is selected from at least one of microcrystalline wax and stearic acid; The EVA is selected from at least one of EVA7470M, EVA360, and EVA7350.
2. The elastic body according to claim 1, characterized in that The preparation method of the elastomer comprises: mixing a high temperature nucleating agent with EVA, heating, stirring and dissolving, adding a processing aid, continuing stirring, cooling and granulating to obtain the elastomer.
3. A midsole, characterized in that: By weight, it contains the following ingredients: The EVA is selected from at least one of EVA7470M, EVA360, and EVA7350; The POE is selected from at least one of ENGAGE8003, ENGAGE8440, and ENGAGE8200.
4. The midsole according to claim 3, characterized in that: The calcium carbonate composition is prepared by mixing calcium carbonate and EVA in a mass ratio of 1:1, kneading, and granulating; The titanium dioxide composition is prepared by mixing titanium dioxide and EVA in a mass ratio of 3:2, kneading and granulating.
5. The midsole according to claim 3, characterized in that: The LH-DH9-CMP is prepared by mixing azodicarbonamide, zinc stearate, chlorosulfonated polyethylene, petroleum resin, and ethylene-vinyl acetate copolymer in a mass ratio of 50:15:5:5:25, kneading, and granulation; The LH-CAT is prepared by mixing zinc oxide, urea ester, calcium carbonate and ethylene-vinyl acetate copolymer in a mass ratio of 30:5:10:55, kneading and granulating.
6. A method for preparing the midsole according to any one of claims 3 to 5, characterized in that: The following steps are involved: Step 1: EVA, POE, elastomer, calcium carbonate composition, titanium dioxide composition, di-tert-butyl peroxide diisopropylbenzene, stearic acid, LH-DH9-CMP, and LH-CAT are mixed and kneaded to obtain a rubber compound; Step 2: Add the mixed rubber into a foaming mold, vulcanize, cool and shape, and obtain a foamed product; Step 3: Add the foamed product into a mold, perform hot pressing and cold pressing, and obtain a midsole; Wherein, the hot pressing time is 480s, and the cold pressing time is 400s.
7. The method for preparing the midsole according to claim 6, characterized in that: The mixing temperature of step 1 is 115-120° C. and the mixing time is 10-15 minutes.
8. The method for preparing the midsole according to claim 6, characterized in that: The vulcanization temperature of step 2 is 165-170° C., and the vulcanization time is 10-12.5 min.
9. The method for preparing the midsole according to claim 6, characterized in that: In step 3, the hot pressing temperature is 165-170°C, and the cold pressing temperature is 15-20°C.
